Adaptive control of a switched hypersonic vehicle model robust to scramjet choking and elevator fault. (December 2019) - An, Hao; Xia, Hongwei; Ma, Guangcheng; Wang, Changhong
Abstract: This paper studies the longitudinal control problem for air-breathing hypersonic vehicles (AHVs) with safety considerations on scramjet choking and elevator fault. A control-oriented switched model (COSM) is employed to better describe the full-envelope flight of AHVs. Unlike the recent control strategy that utilizes neural networks to approximate the unpredictable switching nonlinearities in the COSM, a control strategy free of neural networks is proposed for AHVs. The saturation characteristic of fuel-to-air equivalent ratio is accommodated to protect the scramjet from thermal choking by constructing an adaptive velocity reference generator, which adjusts the velocity reference according to the saturation level. Meanwhile, the time-varying efficiency ratio and bias of faulty elevator are lumped into the uncertain parameters, which are handled by a bound adaption mechanism. A simulation study verifies the developed control. Highlights: COSM-based control is presented for full-envelope flight of AHVs, without using NNs. Scramjet choking and elevator fault are considered. Uncertain parameters in COSM are handled.